Embedded value systems in sustainability assessment tools and their implications. - Gasparatos, A (2010)
This paper explores the implications that arise with the selection of specific sustainability evaluation tools. Sustainability evaluation tools are conceptualized in this paper as value articulating institutions and as such their choice is a far from a trivial matter. In fact their choice can entail various ethical and practical repercussions. However, in most cases the choice of the evaluation tool is made by the analyst(s) without taking into consideration the values of the affected stakeholders. By choosing the analytical tool the analyst essentially "subscribes to" and ultimately "enforces" a particular worldview as the legitimate yardstick to evaluate the sustainability of a particular project (or policy). Instead, this paper argues that the selection of evaluation tools should be consistent with the values of the affected stakeholders. With this in mind, different sustainability evaluation tools' assumptions are critically reviewed and a number of suggestions that could facilitate the choice of the most appropriate tool according to the context of the sustainability evaluation are provided. It is expected that conscious evaluation tool selection, following the suggestions made in this paper, will reduce the risk of providing distorted sustainability evaluations.